Cu-Ni Bimetallic Nanoparticles Anchored on Halloysite Nanotubes for the Environmental Remediation - Singh, D; Vivas, L (Elsevier B.V., 2023)
Hereby, we report the synthesis of CuNi bimetallic nanoparticles (NPs)-decorated halloysite nanotubes (CuNi/HNTs) for the catalytic reduction of 4-nitroaniline (4-NA) and rhodamine B (RhB) dye in an aqueous medium at room temperature. In this work, CuNi/HNTs composites with different wt% of CuNi NPs were synthesized and characterized by various techniques such as SEM, EDS, XRD, TEM and XPS. The TEM characterization confirmed that the CuNi bimetallic NPs (∼ 11 nm) were successfully anchored onto the outer surface of HNTs. Among the prepared catalysts, Cu0.75Ni0.25/HNTs catalyst displayed highest catalytic activity in the reduction of 4-NA to its corresponding amino derivative in the presence of NaBH4 with a maximum conversion efficiency of >99% and an apparent rate constant kapp of 0.152 s−1 within 30 s of reaction time. Notably, even after 15 cycles of catalytic reduction of 4-NA and RhB, there was no apparent deactivation of the catalytic activity of the Cu0.75Ni0.25/HNTs catalyst, demonstrating the excellent catalytic reusability and stability. The presence of CuNi NPs with low Ni content enhanced the catalytic activity due to the synergetic effect. Moreover, the continuous flow fixed bed reactor designed with Cu0.75Ni0.25/HNTs catalyst exhibited the potential application for the reduction of 4-NA and RhB dye under mild reaction conditions. Furthermore, the present catalytic system could be applicable for the treatment of various wastewater effluents. © 2023